2005
DOI: 10.1590/s1413-70542005000400020
|View full text |Cite
|
Sign up to set email alerts
|

Teor de proteína no metabolismo do nitrogênio e da energia em suínos durante o crescimento

Abstract: RESUMOO experimento foi realizado no DZO/UFLA com o objetivo de avaliar os efeitos do teor de proteína bruta no metabolismo do nitrogênio e energia em suínos durante o crescimento. Foram utilizados 12 suínos machos castrados, alojados individualmente em gaiolas de estudo de metabolismo e os tratamentos utilizados consistiram de rações isoenergéticas e isolisínicas, formuladas segundo o conceito de proteína ideal, para atender os teores de proteína bruta 16, 14, 12 e 10% . A quantidade de ração fornecida foi 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There was a reduction of approximately 9.5% in the urinary nitrogen for every percentage point reduced in the protein content of the diets; , Canh et al (1998), andOliveira et al (2005) found values close to 11%.…”
Section: Resultsmentioning
confidence: 83%
“…There was a reduction of approximately 9.5% in the urinary nitrogen for every percentage point reduced in the protein content of the diets; , Canh et al (1998), andOliveira et al (2005) found values close to 11%.…”
Section: Resultsmentioning
confidence: 83%
“…According to Oliveira et al (2005), several factors affect digestibility, including the absence of endogenous enzymes required for he fiber digestion in the pig digestive system. Santos et al (2005) reported that the gastrointestinal tract of the pig is not capable to store large amounts of food, causing an increased rate of digesta passage through the gastrointestinal tract and less contact time between digesta and digestive enzymes and absorptive cells of the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Some works have shown that nutrient manipulations in diets can influence the performance (AROUCA et al, 2007;ZANGERONIMO et al, 2009), nitrogen metabolism (OLIVEIRA et al, 2005;ZANGERONIMO et al, 2007a), physiologic parameters (ZANGERONIMO et al, 2007b) and carcass composition of swine .…”
mentioning
confidence: 99%